Combined effects of quercetin and sodium chloride concentrations on wheat gliadin structure and physicochemical properties. (2nd November 2020) - Wang, Qiming; Tang, Yuwan; Yang, Yaxuan; Lei, Lin; Zhao, Jichun; Zhang, Yuhao; Li, Lin; Wang, Qiang; Ming, Jian
Abstract: BACKGROUND: Polyphenols may interact with protein via covalent bonds and non‐covalent interactions, improving the structures and functional properties of the protein. The cross‐linking between the polyphenol and protein is susceptible to salt (sodium chloride, NaCl) concentrations. Our study investigated the combined effects of quercetin (Q) and NaCl concentrations on wheat gliadin (G) structure and physicochemical properties. RESULTS: Q and NaCl addition resulted in a more compact protein microstructure. The improved foaming and emulsifying properties indicated that the modified G might be potent as a novel surface‐active agent. Differential scanning calorimetry analysis indicated that Q protected the thermal stability from destruction at 50 and 200 mmol L −1 NaCl concentrations, with narrower protein denaturation peaks. Fourier transform infrared and the Raman spectral analyses showed the secondary structural and microenvironmental changes of G. NaCl addition imparted a rearrangement of hydrogen bonds in the polypeptide chain and the disorder of protein structure, whereas Q enhanced the transition from β ‐sheets and random coils to α ‐helices and β ‐turns, forming a more ordered structure. Moreover, the interaction between G and Q resulted in significant disulfide bridges conformational rearrangements in the protein. CONCLUSION: The results showed the benefits of natural food additives in food processing, which might have potential in improving the structure and physicochemical properties of protein‐based foods. © 2020 Society of Chemical Industry